Glandulosa by chloroform and toxicity effect on whit fly (Bemisia, Tabci) which affect vegetables and agricultural crops - Moustapha, Chahid; Moustapha, Oula; Tobal, Zainab (Latakia University Journal -Basic Sciences Series, 2019)
Chemical composition of the Ailanthus Glandulosa leaves extract by chloroform , was determined by GC/MSand UV-spectrum . The extract obtained by Soxhlet, contain 22 components, accounting for 88,04% . The major components determined were 11,13% n,n-di propenyl N- iso propyl , 8,76% silane tetrakis (phenyl ethynyl) , 4,78% cholestane,3-methoxy (beta,5.alpha) , 2,12% purine-6 (1H)-thione, 3,7-dimethyl seleno Effect of the extract on the white fly scattered on eggplant plant where it was found to have an effective effect when focusing 1%,2%,3% on all phases of the insect